A review of the use of ark sites and associated conservation measures to secure the long‐term survival of White‐clawed crayfish Austropotamobius pallipes in the United Kingdom and Ireland. Issue 1 (10th May 2017) - Nightingale, J.; Stebbing, P.; Sibley, P.; Brown, O.; Rushbrook, B.; Jones, G.
Abstract : In response to the global decline of the White‐clawed crayfish Austropotamobius pallipes, key conservation strategies have been developed in the United Kingdom and Ireland, including the supplementation of existing populations and establishment of new populations, using captive‐breeding methods and/or translocations. The South West Crayfish Partnership (SWCP), a group of UK‐based conservation organizations, oversees population‐enhancement programmes in south‐west England. Since 2006 the SWCP has established 16 ark sites (safe refuges) and conducted one river supplementation. In total, 17 sites have been stocked with over 5000 translocated and captive‐hatched A. pallipes, increasing the number of discrete in situ populations in the region by at least 75%. A similar programme in southern Wales, led by Natural Resources Wales, has restocked three river catchments and one English still‐water site with a total of over 4700 captive‐reared juvenile A. pallipes . Although many of these ark sites are newly established, preliminary monitoring results are encouraging; at least 75% of ark sites in south‐west England are currently viable and the three Welsh sites that have been monitored so far suggest continued presence of White‐clawed crayfish. Abstract : In response to the global decline of the White‐clawed crayfish Austropotamobius pallipes, the South West Crayfish Project and South East Wales Crayfish Project were set up in 2008. These partnerships established ark sites (safe refuges) for A. pallipes throughout south‐west England and south Wales, utilizing both lentic (still‐water) and lotic (river) sites. Early results are promising and, at the time of writing, over 75% of the ark sites established are viable. (Photo: Kenrina Maidment, all rights reserved)